Прийменникова префіксація в системі словотвору давньогрецької мови - Чекарева, Є.С. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2005)
В статье рассматриваются проблемы функционирования предлогов в роли приставок в древнегреческом языке, анализируются существующие работы по данному вопросу, определяются стратегические направле ния дальнейших исследований предложной префиксации в древнегреческом языке с учетом формирования новой парадигмы знания в современной лингвистике. The article deals with problems of functioning of prepositions as prefixes in Ancient Greek. The existent papers on this question are studied, the strategic directions of the further research of the prepositional prefixation in Ancient Greek are determined taking into account the formation of the new paradigm of knowledge in contemporary linguistics.
Keywords: давньогрецька мова; прийменникова префіксація; словотворення